Measurements of the branching fractions of the decays B0s→D[mp]sK± and B0s→D−sπ+ - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Britsch, Markward; Blouw, Johan; Dordei, Francesca; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Jäger, Andreas; Kreplin, Katharina; Krocker, Georg Alexander; et al. (Journal of high energy physics, 2012)
The decay mode B0s→D∓sK±Bs0→Ds∓K± B_s^0 \to D_s^{ \mp }{K^{\pm }} allows for one of the theoretically cleanest measurements of the CKM angle γ through the study of time-dependent CP violation. This paper reports a measurement of its branching fraction relative to the Cabibbo-favoured mode B0s→D−sπ+Bs0→Ds−π+ B_s^0 \to D_s^{ - }{\pi^{ + }} based on a data sample corresponding to 0.37 fb−1 of proton-proton collisions at s√=7TeVs=7TeV \sqrt {s} = 7\;{\text{TeV}} collected in 2011 with the LHCb detector. In addition, the ratio of B meson production fractions f s /f d , determined from semileptonic decays, together with the known branching fraction of the control channel B 0 → D −π+, is used to perform an absolute measurement of the branching fractions:B(B0s→D−sπ+)=(2.95±0.05±0.17+0.18−0.22)×10−3,B(B0s→D∓sK±)=(1.90±0.12±0.13+0.12−0.14)×10−4,B(Bs0→Ds−π+)=(2.95±0.05±0.17−0.22+0.18)×10−3,B(Bs0→Ds∓K±)=(1.90±0.12±0.13−0.14+0.12)×10−4, \begin{gathered} \mathcal{B}\left( {B_s^0 \to D_s^{ - }{\pi^{ + }}} \right) = \left( {2.95\pm 0.05\pm 0.17_{{ - 0.22}}^{{ + 0.18}}} \right) \times {10^{{ - 3}}}, \hfill \\ \mathcal{B}\left( {B_s^0 \to D_s^{ \mp }{K^{\pm }}} \right) = \left( {1.90\pm 0.12\pm 0.13_{{ - 0.14}}^{{ + 0.12}}} \right) \times {10^{{ - 4}}}, \hfill \\ \end{gathered} where the first uncertainty is statistical, the second the experimental systematic uncertainty, and the third the uncertainty due to f s /f d .
Im Titel werden "0" und "s" untereinander geschrieben: "0" hochgestellt, "s" tiefgestellt
Im Titel werden "-","+" und "s" untereinander geschrieben: "-","+" hochgestellt, "s" tiefgestellt
Im Titel werden "-"und "s" untereinander geschrieben: "-" hochgestellt, "s" tiefgestellt
The LHCb Collaboration: R. Aaij, S. Bachmann, A. Bien, J. Blouw, M. Britsch, F. Dordei, F. Eisele, C. Fäber, S. Hansmann-Menzemer, A. Jaeger, K. Kreplin, G. Krocker, C. Linn, J. Marks, M. Meissner, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, S. Wandernoth, D. Wiedner, A. Zhelezov [und weitere]
Gesehen am 31.10.2018